Increasing Anaerobic Endurance Using Strength Endurance Training and Continuous Running on Muscular Endurance - Iik Hajarudin; Rahmat Gunawan; Fikri Naufal Zain; Krisno Giovanni; Puji Astuti; Jeki Purnama Putra; Muhammad Zulfikar Romdona (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The aim of this study was to determine whether continuous running training, power endurance, and muscle endurance affect the increase in anaerobic endurance. This research method uses an experimental design. The sample used in this study were SSB Darma Sakti football athletes, Kuningan Regency, with a total of 16 people aged 17 years, taken using a non-probability technique, namely quota sampling. The research design uses a Two Group Pretest Posttest design. The first group was trained using continuous running exercises with power endurance and the second group used continuous running exercises with muscular endurance. The instrument in this study used a 300-meter running test to calculate lactacid anaerobic endurance in order to see changes before and after being given treatment. Processing of the data that has been obtained in the study is then processed using SPSS (Paired Sample T-Test) software. The results of the study showed that continuous running training with power endurance and continuous running with muscle endurance resulted in significant improvements in anaerobic endurance. This study contributes to the development of football-specific training models and provides a foundation for future research to explore longer training durations, varied age groups, or the integration of mental and tactical components alongside physical conditioning to further optimize anaerobic performance.